Fifty years after the discovery of the association of HLA B27 with ankylosing spondylitis - Joachim Sieper; Juergen Braun (RMD Open)
The human lymphocyte antigen B27 (HLA B27) is a member of the HLA class I family of genes in the major histocompatibility complex whose name goes back to its discovery in studies of transplanted tissue compatibility. Its prevalence in the mid-European population is about 8%. The association of HLA B27 alleles with ankylosing spondylitis (AS), a highly heritable disease, which is part of the spectrum of axial spondyloarthritis (axSpA), was discovered 50 years ago. HLA B27 explains less than 30% of the total genetic load. About 60%–90% of axSpA patients worldwide carry HLA B27. The prevalence of the disease is linked to the frequency of HLA B27 in the population which implies that there are relevant differences. Among the roughly 200 subtypes known there are two which are not disease associated. The function of HLA class I molecules is to present peptides to the immune system to defend the organism against microbes targeted by CD8+T cells. This is much supported by the role of the endoplasmic reticulum aminopeptidase 1 (ERAP 1) in AS, an enzyme that is responsible for the intracellular trimming of peptides, since polymorphisms of this gene are only associated with HLA-B27+ disease. The arthritogenic peptide hypothesis trying to explain the pathogenesis of AS is based on that very immune function assuming that also self peptides can be presented. HLA-B27 also plays an important role in classification, diagnosis and severitiy of axSpA.